2020
DOI: 10.17738/ajes.2020.0012
|View full text |Cite
|
Sign up to set email alerts
|

Conodont thermometry by Raman spectroscopy on carbonaceous material: a case study from the Northern Calcareous Alps (Mürzalpen Nappe, Eastern Alps)

Abstract: Carnian metapelites from the southeastern segment of the Mürzalpen Nappe (Northern Calcareous Alps, Eastern Alps) were heated to 280-310 °C, estimated by Raman spectroscopy of carbonaceous material (RSCM). This temperature range is correlated to a Color Alteration Index of 5.0-6.5, determined on conodonts from adjacent Anisian to Norian carbonates. Average RSCM temperatures estimated on the conodonts are biased towards higher temperatures. The spectral characteristics of the conodont apatite suggest a composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(68 reference statements)
1
0
0
Order By: Relevance
“…3). Remarkably, the correlation between CAI and RSCM temperatures resembles the correlation established for Triassic conodonts (Rantitsch et al, 2020b).…”
Section: Discussionsupporting
confidence: 71%
“…3). Remarkably, the correlation between CAI and RSCM temperatures resembles the correlation established for Triassic conodonts (Rantitsch et al, 2020b).…”
Section: Discussionsupporting
confidence: 71%
“…Both slope and intercept differed significantly between these two datasets at a confidence level of 0.05. In contrast, our dataset and that by Zhang et al 15 showed strong clustering close (Zhang et al) or directly on the regression line fitted to the values measured by Rantitsch et al 42 . Compared to the other studies, positions of the ν 1 -PO 4 3− band measured for our specimens showed consistently high values with a mean of 964.00 (median 963.99, standard deviation 0.13, n = 30).…”
Section: Resultssupporting
confidence: 48%
“…5 ). The datasets by both McMillan and Golding 41 and Rantitsch et al 42 showed high variability in the position and widths of the ν 1 -PO 4 3− band. Model II regression was fitted to the relationship for these two datasets, producing slopes equal to −0.92 (R 2 = 0.63, N = 41) and −1.30 (R 2 = 0.90, N = 153), respectively (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations